PENGUATAN PEMAHAMAN KEAGAMAAN JAMAAH MASJID SEBAGAI BASIS PENDIDIKAN ISLAM DI GRESIK - Sya'bani, Mohammad Ahyan Yusuf (Universitas Muhammadiyah Tapanuli Selatan, 2022)
There is no doubt that Gresik is famous as a center of industry, pesantren, trade and crafts. This makes Gresik more congested and complex problems. On the other hand, Gresik is a cultural city, pesantren, and mayor city which is reflected in the cultural behavior and customs of its people in preserving the heritage of their predecessors both from religious and traditional issues. In this regard, the pilgrims of the at-Taqwa Giri mosque who live in the Gresik area feel that they have been in a comfort zone with the gresik community population including the Muslim-majority Kebomas District. As a dominant religion this can be an advantage. However, it is not as a guarantee to measure the level of religious understanding (Islam), in fact, sometimes the understanding and practice are also still very lacking due to the too high mobility of urban activities, especially in urban Gresik. The lack and lack of understanding related to Islamic religious material at the jama'ah of the at-Taqwa Giri mosque in Kebomas makes it important to organize a special program to strengthen religious understanding in this case is in the form of recitation of mosque pilgrims who have a diversity of life history, but do not reduce their motivation to study Islamic teachings